RNA Editing Responses to Oxidative Stress between a Wild Abortive Type Male-Sterile Line and Its Maintainer Line - Xiong, Jie; Tao, Tao; Luo, Zhi; Yan, Shuaigang; Liu, Yi; Yu, Xinqiao; Liu, Guolan; Xia, Hui; Luo, Lijun (Frontiers in Plant Science, 2017)
RNA editing of mitochondrial gene transcripts plays a central role during plant development and evolutionary adaptation. RNA editing has previously been reported to differ between the rice cytoplasmic male sterile (CMS) line and its maintainer line, which has been suggested as a cause for their different performances under environmental stress. To specifically test this hypothesis, a wild abortive (WA) CMS line (Huhan-1A) and its maintainer line (Huhan-1B) were utilized to investigate performances in response to oxidative stress, as well as RNA editing efficiencies on transcripts of six selected mitochondrial genes. Compared to the maintainer line, Huhan-1A represented both lower plant height and total antioxidant capacity, possessed higher total soluble protein and chlorophyll contents, accumulated less H2O2 content on the 3rd day after treatment (DAT), and exhibited higher survival ratio after re-watering. Furthermore, a total of 90 editing sites were detected on transcripts of six mitochondrial genes (atp9, nad2, nad7, nad9, ccmB, and ccmC) in both Huhan-1A and Huhan-1B on the 0, 1st, and 3rd DAT. Forty-eight sites were furthermore determined as stress-responsive sites (SRS). Generally, in response to oxidative stress, SRS in Huhan-1A increased the resulting editing efficiencies, while SRS in Huhan-1B decreased the resulting editing efficiencies. In addition, 33 and 22 sites at ccmB and ccmC were differentially edited between Huhan-1A and Huhan-1B, respectively, on the 0, 1st, and 3rd DAT. Editing efficiencies of ccmB and ccmC were generally lower in Huhan-1A (ccmB, 37.3-47.8%; ccmC, 41.2-52.3%) than those in Huhan-1B (ccmB, 82.6-86.5%; ccmC, 81.0-82.9%). Deficiencies of RNA editing in Huhan-1A at ccmB and ccmC could lead to the loss of transmembrane domains in their protein structures. Consequently, differences in RNA editing at ccmB and ccmC between the WA-CMS line and its maintainer line partially explained their different performances under stress. Moreover, we detected differences in expressions of pentatricopeptide repeat (PPR) genes between both lines, as well as significant correlations with RNA editing. Our study indicated potential associations of RNA editing and PPR genes in rice tolerance to abiotic stresses. However, the underlying molecular mechanisms of stress-adaptation, which are attributed to RNA editing on transcripts of mitochondrial genes, require further